Quaternary aluminum amorphous nanocrystalline powder as well as preparation method and application thereof
Through the real air atomization legal system to prepare four -dollar aluminum ullen nanocrystalline powder, the problem of the pink particle size and composition of aluminum -based amorphous nanocrystalline materials in existing technologies has been solved. Sexual non -crystal nanocrystalline powder is suitable for the application of corrosion -resistant equipment in the marine environment.
Patent Information
- Application Number
- CN202411418047.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, aluminum-based amorphous nanocrystalline materials are mainly used in the form of coatings on the surface of equipment structural parts, and the powder particle size and composition are uneven during the preparation process, which limits the application efficiency and performance of the material.
Use real air atomization legal system to prepare four -dollar aluminum amyl crystal nanocrystalline powder. The electromagnetic induction melting and high -voltage pheasant atomization treatment is controlled to control the composition and particle size distribution of the powder to ensure that the ball shape is high and the oxygen content is low. Crystal structure.
The prepared quantum aluminum amorphous nanocrystalline powder has excellent corrosion resistance and liquidity, and is suitable for technologies such as hot spraying and laser melting to meet the needs of corrosion -resistant equipment in the marine environment.
Smart Images

Figure CN119368727A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of powder metallurgy, and in particular to a quaternary aluminum amorphous nanocrystalline powder and a preparation method and application thereof. Background Art
[0002] Amorphous alloy materials do not contain the crystal structure of ordinary metal alloy materials, and exhibit excellent strength, hardness, corrosion resistance, wear resistance and other performance characteristics, and have great application potential in extreme environment structural applications. The crystals in nanocrystalline materials are nanoscale in size, and there are a large number of grain boundaries in the structure. Due to their small size effect, they also have high strength, high hardness, and other performance characteristics, and local nanocrystallization also helps to improve the corrosion resistance of the material. Therefore, amorphous nanocrystalline materials, as structural materials for equipment or devices, have excellent application prospects in the fields of vehicles, oceans, chemicals, machinery, and so on. In particular, aluminum-based amorphous nanocrystalline materials have the characteristics of low density, high strength, strong toughness, good corrosion resistance and wear resistance, low expansion coefficient, and strong amorphous forming ability. They are especially suitable for anti-corrosion applications on the surface of structural parts of marine environment equipment.
[0003] At present, aluminum-based amorphous nanocrystalline materials are mainly used in the form of coatings on the surfaces of equipment structural parts. Spherical powder is the raw material for the application of this material. At present, the preparation of amorphous nanocrystalline powder mainly includes methods such as plasma spheroidization and vacuum air atomization. Factors such as the composition and amorphous content of aluminum-based amorphous nanocrystalline determine the application performance of the material, and factors such as the powder particle size formed during the preparation process also determine the preparation efficiency and composition. The above two points are also the key to restricting the application of aluminum-based amorphous nanocrystalline materials. At present, there is an urgent need to provide a quaternary aluminum amorphous nanocrystalline powder and a vacuum air atomization preparation method thereof. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a quaternary aluminum amorphous nanocrystalline powder and a preparation method and application thereof.
[0005] In the first aspect, the quaternary aluminum amorphous nanocrystalline powder provided by the present invention comprises the following components in atomic percentage: Al 70-95at.%, Ni 3-15at.%, Zr 1-5at.%, Si 1-10at.%. The aluminum-based amorphous nanocrystalline powder provided by the present invention has high sphericity and low oxygen content, can be used as a raw material for thermal spraying, laser cladding and other technologies, has excellent corrosion resistance, and meets the requirements of corrosion-resistant equipment in marine environments; the alloy components selected by the design of the present invention are moderately priced, and the preparation method thereof is simple and easy to implement, and can be used as a new type of corrosion-resistant surface protective material.
[0006] Preferably, in the quaternary aluminum amorphous nanocrystalline powder, Al accounts for 75-85 at.%, Ni accounts for 8-10 at.%, Zr accounts for 4-5 at.%, and Si accounts for 3-10 at.%.
[0007] Preferably, in the quaternary aluminum amorphous nano-gold alloy powder, the amorphous content of particles with a particle size of less than 25 μm is 30-40%, the amorphous content of particles with a particle size of 25-50 μm is 20-30%, and the amorphous content of particles with a particle size of more than 50 μm is 10-20%. The crystallization temperature of the quaternary aluminum amorphous nano-gold alloy powder is 321-338°C.
[0008] Preferably, the average particle size of the quaternary aluminum amorphous nano-gold alloy powder is 15-25 μm, preferably 20-22 μm, and the particle size distribution is 5-80 μm.
[0009] Further preferably, the quaternary aluminum amorphous nano-gold alloy powder is a spherical powder; preferably, the sphericity of the quaternary aluminum amorphous nano-gold alloy powder is greater than 90%, the oxygen content is less than 100ppm, the amorphous content of the particle size below 25μm is 30~40%, the amorphous content of the particle size 25-50μm is 20~30%, the amorphous content of the particle size above 50μm is 10~20%, and the crystallization temperature is 321~338℃.
[0010] In the present invention, by adopting the above-mentioned screening of oxygen content and particle size, it is possible to better obtain alloy powder that meets the original design and is suitable for spraying or laser cladding, and further by screening the sphericity, amorphous content and crystallization temperature, it is possible to better obtain powder with high fluidity that can be used to prepare amorphous nanocrystalline coatings.
[0011] In a second aspect, the present invention provides a method for preparing the quaternary aluminum amorphous nanocrystalline powder, which is prepared by a vacuum gas atomization method; preferably, the method comprises the following steps: 1) The raw materials of Al, Ni, Zr and Si are surface treated.
[0012] 2) The raw materials processed in step 1) are subjected to electromagnetic induction melting to obtain molten metal.
[0013] 3) The high-pressure airflow and the molten metal are sprayed out simultaneously to perform gas atomization treatment to obtain alloy powder.
[0014] 4) The alloy powder is sieved after cooling.
[0015] Preferably, in step 1), the surface treatment includes grinding the particles or block raw materials to remove surface oxides, ultrasonic cleaning with acetone or alcohol for 30-40s, repeating the cleaning 1-3 times to remove surface impurities; and then drying under vacuum conditions at a drying temperature of less than 150°C to prevent oxidation.
[0016] Preferably, in step 2), the vacuum degree of the smelting chamber of the electromagnetic induction smelting is less than 1.0×10 -5Pa, and then introduce atomizing gas; preferably, the atomizing gas is argon with a pressure of 6-8 MPa; and / or, the melting temperature is 1700-2000°C, preferably 1800-1900°C. During the electromagnetic induction melting process, the vacuum degree of the melting chamber is maintained below 1.0×10 -5 Pa, the introduction of atomizing gas argon helps to reduce oxidation and impurities and ensure the purity of the material. At the same time, the smelting is set in the optimal temperature range, which can melt the metal raw materials better and more evenly, and help improve the smelting efficiency and quality. These conditions work together to ensure the quality and performance of the final product.
[0017] Further preferably, in step 3), during the atomization treatment, the pressure of the high-pressure argon gas flow is 6-8 MPa.
[0018] Further preferably, in step 4), the powder obtained by the aerosol treatment is cooled, sieved and dried to obtain quaternary aluminum amorphous nanocrystalline powder with a particle size distribution of 5-80 μm and an average particle size of 15-25 μm.
[0019] In the present invention, the average particle size of the quaternary aluminum amorphous nanocrystalline powder obtained by treatment is in the range of 15-25 μm; the particle size is preferably selected to be less than 75 μm, so as to obtain a surface protective coating suitable for preparing a surface protective coating with excellent corrosion resistance.
[0020] In a third aspect, the present invention provides the use of the above-mentioned quaternary aluminum amorphous nanocrystalline powder or the quaternary aluminum amorphous nanocrystalline powder obtained by the above-mentioned preparation method in the preparation of anti-corrosion coatings for metal components suitable for marine environments, 3D laser cladding, cold spraying or hot spraying.
[0021] The beneficial effects of the present invention are at least as follows: 1) In terms of alloy powder composition, the Al element in the present invention is the basic element, and the Al and Ni strong corrosion-resistant elements are used as the main components of the amorphous nanocrystalline powder to enhance the corrosion resistance of the material in the marine environment. By adding the Zr element, the recrystallization process of Al can be hindered, the grains can be refined, and the formation of nanocrystals can be achieved. In addition, the Zr and Si elements also have a certain strengthening and improving effect on the mechanical properties of the aluminum-based quaternary amorphous nanocrystalline powder, and can further improve the corrosion resistance of the powder. At the same time, by controlling the addition content of elements such as Ni and Zr, the lightweight of the powder component is guaranteed. The alloy powder composition of the present invention meets the corrosion resistance requirements of the material and makes the alloy powder tend to form an amorphous nanocrystalline structure. 2) In terms of the preparation method of the alloy powder, the vacuum gas atomization method has a simple preparation process flow, high powder formation efficiency, and the obtained powder composition is uniform, high sphericity, and low oxygen content. It can be used as a raw material in industries such as 3D laser cladding and cold / hot spraying. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 This is a SEM image of the Al75Ni10Zr5Si10 amorphous nanocrystalline powder of Example 1 of the present invention.
[0024] Figure 2 This is the XRD diagram of the Al75Ni10Zr5Si10 amorphous nanocrystalline powder of Example 1 of the present invention.
[0025] Figure 3 This is the DSC graph of the Al75Ni10Zr5Si10 amorphous nanocrystalline powder of Example 1 of the present invention.
[0026] Figure 4 This is a SEM image of the Al85Ni8Zr4Si3 amorphous nanocrystalline powder of Example 2 of the present invention.
[0027] Figure 5 This is the XRD diagram of the Al85Ni8Zr4Si3 amorphous nanocrystalline powder of Example 2 of the present invention.
[0028] Figure 6 It is the DSC graph of the Al85Ni8Zr4Si3 amorphous nanocrystalline powder of Example 2 of the present invention.
[0029] Figure 7 This is a SEM image of the Al80Ni10Zr4Si6 amorphous nanocrystalline powder of Example 3 of the present invention.
[0030] Figure 8 This is the XRD diagram of the Al80Ni10Zr4Si6 amorphous nanocrystalline powder of Example 3 of the present invention.
[0031] Fig. 9 This is the DSC graph of the Al80Ni10Zr4Si6 amorphous nanocrystalline powder of Example 3 of the present invention.
[0032] Fig.10 It is a SEM picture of the Al87Ni7Zr5Si1 amorphous nanocrystalline powder of comparative example 1 of the present invention.
[0033] Fig.11 It is the XRD diagram of the Al87Ni7Zr5Si1 amorphous nanocrystalline powder of comparative example 1 of the present invention.
[0034] Fig.12It is the DSC graph of the Al87Ni7Zr5Si1 amorphous nanocrystalline powder of comparative example 1 of the present invention. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer is not specified for the instruments used, they are all conventional products that can be purchased through regular channels. The methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this field or the product instructions are used.
[0037] The quaternary aluminum-based amorphous nanocrystalline powder provided by the embodiment of the present invention has a better sphericity than other powders. At the same time, since the alloy powder is composed of highly corrosion-resistant elements, the coating material prepared using this series of alloy powders is expected to have excellent corrosion resistance. At the same time, the alloy powder prepared by vacuum gas atomization has a fast cooling rate, so that the powder forms an amorphous nanocrystalline structure. The quaternary aluminum amorphous nanocrystalline powder includes the following components in atomic percentage: Al 70-95at.%, Ni 3-15at.%, Zr 1-5at.%, Si 1-10at.%. Specifically, the Al, Ni, Zr, and Si raw materials used in the preparation of the powder by the present invention are all commercially available bulk raw materials with a purity higher than 99 wt%.
[0038] The embodiment of the present invention provides a method for preparing quaternary aluminum amorphous nanocrystalline powder by vacuum gas atomization, comprising washing and drying the raw materials, and repeatedly vacuum electromagnetic induction melting all the constituent elements to obtain a uniform molten metal, and then simultaneously spraying a high-pressure argon gas flow and the molten metal to achieve atomization, taking out the atomized powder, and sieving it to obtain the quaternary aluminum amorphous nanocrystalline powder. In an optional embodiment, when performing induction melting, the vacuum degree of the equipment is less than 1.0×10 -5 Pa, argon is filled before smelting, the induction heating power supply is started, and the heating power is adjusted to make the temperature reach 1700° C.-2000° C. In an optional embodiment, the pressure of the high-pressure argon gas flow during the vacuum gas atomization powder making process is 6-8 MPa.
[0039] The following Examples 1-2 are for preparing the microscopic morphology, microstructure and glass transition temperature of quaternary aluminum amorphous nanocrystalline powders of Al75Ni10Zr5Si10 and Al85Ni8Zr4Si3.
[0040] Example 1
[0041] The ingredients are prepared according to the following composition: Al, 75at.%; Ni, 10at.%; Zr, 5at.%; Si, 10at.%.
[0042] Raw material processing: Use industrial materials (purity ≥ 99%) for batching. Before batching, pre-treat the surface of the raw materials, then clean them with alcohol ultrasonic wave, 30~40s ultrasonic cleaning, repeat the cleaning 1-3 times, and then dry the cleaned raw materials in a vacuum drying oven at 80℃ to prevent oxidation.
[0043] Vacuum gas atomization powder making process: the raw materials to be atomized are loaded into the vacuum electromagnetic induction melting furnace of the vacuum gas atomization powder making device. Then the vacuum operation is carried out. When the vacuum degree of the equipment is lower than 1.0×10 -5 When the temperature reaches 1850°C, the vacuum device is turned off and high-purity argon gas is filled in. The pressure of the high-pressure argon gas flow is 7MPa. The temperature is set to 1850°C, and metal smelting is started to melt the metal raw materials evenly. The atomization pressure is adjusted to 7MPa, and the atomization valve and the spray-casting valve are opened to spray the molten metal and the argon gas flow at the same time. The metal droplets are rapidly cooled in an inert gas environment to form spherical particles. After cooling, the spherical particle powder is classified, collected, sieved, and vacuum-packed in an inert gas atmosphere. Finally, a quaternary aluminum-based amorphous nanocrystalline powder is obtained. The powder particle size is 5-75μm, the average particle size is 20μm, the yield is 55%, the sphericity is 95%, and the oxygen content is 66ppm.
[0044] Example 2
[0045] The ingredients are prepared according to the following composition: Al, 85at.%; Ni, 8at.%; Zr, 4at.%; Si, 3at.%.
[0046] Raw material processing: Use industrial materials (purity ≥ 99%) for batching. Before batching, pre-treat the surface of the raw materials, then clean them with alcohol ultrasonic wave, 30~40s ultrasonic cleaning, repeat the cleaning 1-3 times, and then dry the cleaned raw materials in a vacuum drying oven at 80℃ to prevent oxidation.
[0047] Vacuum gas atomization powder making process: the raw materials to be atomized are loaded into the vacuum electromagnetic induction melting furnace of the vacuum gas atomization powder making device. Then the vacuum operation is carried out. When the vacuum degree of the equipment is lower than 1.0×10 -5When the pressure reaches 2000°C, the vacuum device is turned off and high-purity argon gas is filled in. The pressure of the high-pressure argon gas flow is 6MPa. The temperature is set to 2000°C, and metal smelting is started to melt the metal raw materials evenly. The atomization pressure is adjusted to 6MPa for the pressure of the high-pressure argon gas flow, and the atomization valve and the spray-casting valve are opened to spray the molten metal and the argon gas flow at the same time. The metal droplets are rapidly cooled in an inert gas environment to form spherical particles. After cooling, the spherical particle powder is classified, collected, sieved, and vacuum-packed in an inert gas atmosphere. Finally, a quaternary aluminum-based amorphous nanocrystalline powder is obtained. The powder particle size is 5-80μm, the average particle size is 22μm, the yield is 40%, the sphericity is 91%, and the oxygen content is 73ppm.
[0048] Example 3
[0049] The ingredients are prepared according to the following composition: Al, 80at.%; Ni, 10at.%; Zr, 4at.%; Si, 6at.%.
[0050] Raw material processing: Use industrial materials (purity ≥ 99%) for batching. Before batching, pre-treat the surface of the raw materials, then clean them with alcohol ultrasonic wave, 30~40s ultrasonic cleaning, repeat the cleaning 1-3 times, and then dry the cleaned raw materials in a vacuum drying oven at 80℃ to prevent oxidation.
[0051] Vacuum gas atomization powder making process: the raw materials to be atomized are loaded into the vacuum electromagnetic induction melting furnace of the vacuum gas atomization powder making device. Then the vacuum operation is carried out. When the vacuum degree of the equipment is lower than 1.0×10 -5 When the pressure reaches 1000 Pa, the vacuum device is turned off and high-purity argon gas is filled in. The pressure of the high-pressure argon gas flow is 8MPa. The temperature is set to 1700℃, and metal smelting is started to melt the metal raw materials evenly. The atomization pressure is adjusted to 8MPa, and the atomization valve and the spray casting valve are opened to spray the molten metal and the argon gas flow at the same time. The metal droplets are quickly cooled in an inert gas environment to form spherical particles. After cooling, the spherical particle powder is classified, collected, sieved, and vacuum packaged in an inert gas atmosphere. Finally, a quaternary aluminum-based amorphous nanocrystalline powder is obtained. The powder particle size is 8-72μm, the average particle size is 27μm, the yield is 46%, the sphericity is 92%, and the oxygen content is 80ppm.
[0052] Comparative Example 1
[0053] The same method as in Example 1 is adopted, except that the ingredients are prepared according to the following composition: Al, 87 at. %; Ni, 7 at. %; Zr, 5 at. %; Si, 1 at. %.
[0054] The relevant performance tests were carried out on the powders prepared in each example, and the data are summarized in Table 1.
[0055] Table 1 Amorphous content data of quaternary aluminum amorphous nanocrystalline powder prepared in each embodiment.
[0056]
[0057] Combined with Table 1 and Figure 1-12 It can be seen that the powder prepared by the vacuum gas atomization method of the present invention has high sphericity and an amorphous nanocrystalline structure, and can be used as a raw material in laser cladding, thermal spraying and other industries.
[0058] In summary, the quaternary aluminum amorphous nanocrystalline powder and the preparation method thereof described in the present invention can directly prepare amorphous nanocrystalline powder with high sphericity by vacuum gas atomization, and can be applied to surface protection fields such as laser cladding and thermal spraying.
[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A quaternary aluminum amorphous nanocrystalline powder, characterized in that: In terms of atomic percentage, it includes the following components: Al 70-95at.%, Ni 3-15at.%, Zr 1-5at.%, Si 1-10at.%.
2. The quaternary aluminum amorphous nanocrystalline powder according to claim 1, characterized in that: Al 75-85at.%, Ni 8-10at.%, Zr 4-5at.%, Si 3-10at.%.
3. The quaternary aluminum amorphous nanocrystalline powder according to claim 1 or 2, characterized in that: In the quaternary aluminum amorphous nano-gold alloy powder, the amorphous content of particles with a particle size of less than 25 μm is 30-40%, the amorphous content of particles with a particle size of 25-50 μm is 20-30%, and the amorphous content of particles with a particle size of more than 50 μm is 10-20%. The crystallization temperature of the quaternary aluminum amorphous nano-gold alloy powder is 321-338°C.
4. The quaternary aluminum amorphous nanocrystalline powder according to any one of claims 1 to 3, characterized in that: The average particle size of the quaternary aluminum amorphous nano-gold alloy powder is 15-25 μm, and the particle size distribution is 5-80 μm; and / or the quaternary aluminum amorphous nano-gold alloy powder is a spherical powder; preferably, the sphericity of the quaternary aluminum amorphous nano-gold alloy powder is greater than 90%, and the oxygen content is less than 100 ppm.
5. The method for preparing the quaternary aluminum amorphous nanocrystalline powder according to any one of claims 1 to 4, characterized in that: The method is prepared by vacuum atomization, comprising the following steps: 1) The raw materials of Al, Ni, Zr and Si are surface treated; 2) subjecting the raw materials processed in step 1) to electromagnetic induction melting to obtain molten metal; 3) The high-pressure airflow and the molten metal are sprayed out simultaneously to perform gas atomization treatment to obtain alloy powder.
6. The preparation method according to claim 5, characterized in that: In step 1), the surface treatment includes grinding the raw material, ultrasonic cleaning with acetone or alcohol for 30-40 seconds, and then drying under vacuum conditions at a temperature less than 150°C.
7. The preparation method according to claim 5 or 6, characterized in that: In step 2), the vacuum degree of the melting chamber of the electromagnetic induction melting is less than 1.0×10 -5 Pa, then introducing atomizing gas; and / or, the smelting temperature is 1700-2000°C.
8. The preparation method according to any one of claims 5 to 7, characterized in that: In step 3), during the atomization treatment, the pressure of the high-pressure argon gas flow is 6-8 MPa.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The method further comprises step 4), wherein the alloy powder is cooled and then sieved; preferably, the powder obtained by the aerosol treatment is cooled, sieved and dried to obtain quaternary aluminum amorphous nanocrystalline powder with a particle size distribution of 5-80 μm and an average particle size of 15-25 μm.
10. Use of the quaternary aluminum amorphous nanocrystalline powder according to any one of claims 1 to 4 or the quaternary aluminum amorphous nanocrystalline powder obtained by the preparation method according to any one of claims 5 to 9 in the preparation of anti-corrosion coatings for metal components in marine environments, 3D laser cladding, cold spraying or hot spraying.